Scope Of Application of The Scientific Style of Speech, Features and Rules (Texas Journal of Multidisciplinary Studies, 2024)
This article describes the unique aspects of the scientific speech style. Also, the didactic importance of mastering various methods of forming scientific information during the formation of specialists is discussed